College Campus Sexual Assault and Female Students With Disabilities - Campe, Margaret I. (Journal of interpersonal violence, 2021)
College campus sexual assault is well-documented as a pervasive problem among U.S. colleges and universities, with female college students at the greatest risk. Although more than 30 years of research has been dedicated to uncovering college campus sexual assault and identifying risk factors for victimization, few studies have looked at the relationship between female students with disabilities and college campus sexual assault victimization. The present study uses data from the female respondents (N = 22,828) of the American College Health Association’s Fall 2016 National College Health Assessment (ACHA-NCHA) to explore the relationship between female college campus sexual assault victimization and disability status. The analysis finds that disability status produces significantly greater increased odds for sexual assault than other commonly cited risk factors such as binge drinking, drug use, or Greek affiliation. Specifically, female students with disabilities are at increased odds for any type of sexual assault compared with female students without disabilities (odds ratio [OR] = 1.96; p < .001). This increases when looking at specific types of assault. Female students with disabilities were over 100% more likely to experience completed assaults (OR = 2.34; p < .001), attempted assaults, (OR = 2.03; p < .001), and relationship assaults (OR = 2.22; p < .001) compared to female students without disabilities. Analysis also indicates differences in other significant independent variables when sexual assault status is broken down into categories of completed sexual assaults, attempted sexual assaults, and relationship sexual assaults. In addition, the types of disability showing significance vary between the different types of assault. These findings have important policy implications for campus violence prevention and intervention and suggest multiple avenues for further research.